2012
DOI: 10.1097/pec.0b013e3182624906
|View full text |Cite
|
Sign up to set email alerts
|

No Longer a “Nursemaid’s” Elbow

Abstract: Radial head subluxation mechanisms can be classified into subcategories, which may be caregiver and even patient gender specific. Provider awareness regarding these mechanisms may help target education and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
0
8
2
4
Order By: Relevance
“…The diagnosis of pulled elbow depends on history of mechanism and physical examination [ 3 ]. Reduction may be attempted without radiographs if clinical presentation is typical of a pulled elbow [ 7 , 10 ]; however, in case of an unclear mechanism of injury, unnecessary radiographs are often taken [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of pulled elbow depends on history of mechanism and physical examination [ 3 ]. Reduction may be attempted without radiographs if clinical presentation is typical of a pulled elbow [ 7 , 10 ]; however, in case of an unclear mechanism of injury, unnecessary radiographs are often taken [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, spontaneous reduction of ALD was reported for 16% of the children in our study. Rudloe et al reported that spontaneous reduction of ALD was observed in 9.5% of patients, with a further 8% reduction achieved during imaging studies . Children with ALD face an increased risk for recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…По данным крупного поперечного исследования K. Pirruccio et al, выполненного по национальным базам данных за 2001-2017 гг., удельный вес ПГЛ в группах у детей в возрасте до 1 года составил 7 % (ДИ 6,0-8,8 %), от 1 года до 2 лет -33,5 % (ДИ 32,1-35,0 %), от 2 до 3 лет -35,1 % (ДИ 33,7-36,6 %), от 3 до 4 лет -15,6 % (ДИ 14,4-16,8 %), от 4 до 5 лет -5,7 % (ДИ 5,0-6,3 %), от 5 до 6 лет -2,1 % (ДИ 1,7-2,5 %) от 6 до 7 лет -0,7 % (0,4-1,0 %), в возрасте 7 лет -незначительное количество [2]. В большинстве научных работ отмечено преобладание девочек (57-60 %) [2,4,11,14], однако, по данным проспективного исследования F. Heydari et al, в 53 % случаев ПГЛ наблюдалось у мальчиков [10]. Левая рука повреждается чаще правой (60-61 %) [4,10,11].…”
Section: эпидемиологияunclassified
“…Основной и классический механизм ПГЛ заключается в резкой тракции за запястье или кисть при разогнутом локтевом суставе и пронированном предплечье [3,14]. Основу повреждения составляют смещение и интерпозиция в плечелучевом суставе анулярной связки, которая в норме окружает головку и шейку лучевой кости и удерживает головку напротив головчатого возвышения плечевой кости.…”
Section: этиология и патогенезunclassified
See 1 more Smart Citation